SAP R/3 Enterprise Software: An Introduction - Hayen Roger (American : MC Graw Hill, 2006)
This text is written by Dr. Roger Hayen, a SAP R/3 instructor at Central Michigan University, one of three universities in the U.S. to offer SAP R/3 certification for students in an SAP University Alliance program, called “Process Integration Certification Academy”. Hayen’s extensive familiarity with the subject provides a useful introduction to the essential concepts of the SAP R/3 System, with the opportunity for hands-on implementation of those concepts. The text’s succinct, yet thorough coverage makes it versatile, so that it is appropriate for both student instruction and professional training and reference.
Keywords: SAP R/3 Enterprise Software